Measuring Absenteeism - Mikalachki, A.; Gandz, Jeffrey (Relations industrielles / Industrial Relations, 1979)
The purpose of this paper is twofold: to provide a rationale for expending effort on measuring absenteeism and to unravel some of the complexities associated with the measurement and interpretation of absenteeism data.